Selections from Varlık 1933-2008 (2008) Osman Deniztekin (ed.); Sabahattin Eyüboğlu (2008) The Blue and the Black, translated by Hughette Eyüboğlu and Lynne Saka; Bengisu Rona (2008) Orhan Kemal in Jail with Nazım Hikmet. - Laurence Raw (European Journal of Turkish Studies)
This extended review of three recently published English translations of the works of intellectuals such as Nazım Hikmet, Orhan Kemal and Sabahattin Eyüboğlu shows how they emphasized the importance of freedom of thought, in a context that continually sought to suppress them. In the light of recent events, such as the killing of Hrant Dink, the review also suggests that their struggles are as important today as they were seven decades ago.